Trends of ED visits, admissions, and deaths for pediatric traumatic brain injury comparing sport and non-sport mechanisms - Holly R. Hanson; Michael A. Gittelman; Wendy J. Pomerantz (BMC, 2019)
Abstract Background Traumatic brain injuries (TBI) in children result in significant morbidity and mortality. There are many mechanisms, both sport and non-sport related, which cause these injuries. Studies have reported that Emergency Department (ED) visits for pediatric TBI caused by sports are increasing; however, no subsequent study has evaluated the trend in non-sport TBI. The objective of this study was to evaluate ED visits, admissions, and deaths for non-sport TBI compared to those caused by sports. Methods A retrospective study of children 5-19 years of age was performed at a pediatric, level 1 trauma center from 2002 to 2012. Subjects with a primary or secondary diagnosis of TBI were identified from the hospital's trauma registry, and mechanism of injury, disposition, injury severity score, and length of stay were recorded. Frequencies were used to characterize the population, Chi-square analysis was performed to determine differences between groups, and linear trend lines were calculated for sport-related and non-sport TBI by year. Results Thirteen thousand two hundred ninty one subjects were seen in the ED between 2002 and 2012 for a TBI; 9527 (72%) were from a non-sport mechanism, and 3764 (28%) were from a sport mechanism. Subjects with a non-sport TBI were more likely to be younger (p < 0.001), African American (p < 0.001), and have Medicare/Medicaid (p < 0.001). Subjects with a non-sport TBI were admitted to the hospital 15% of the time, and subjects with a sport-related TBI were admitted 10% of the time (p < 0.001). When evaluating all TBI by mechanism of injury, sport had the lowest injury severity score (mean 4.4) and the shortest length of stay (mean 1.6 days) of any mechanism. There were six deaths reported from non-sport TBI and none from sport-related TBI. ED visits for sport-related TBI increased 92%, and non-sport TBI increased 22% over 10 years. There was a peak in TBI, in both groups, seen in 2009. Conclusions ED visits for both sport and non-sport TBI have increased over the past 10 years. TBI from a non-sport mechanism was more likely to result in hospitalization or death. Prevention efforts should be expanded to include all high-risk TBI mechanisms, not just sports.